Relation between some socio economic indicators and the security factor – the case of Algarve - José António Gil Castanho; Maria-Teresa Noronha Vaz (European Regional Science Association (ERSA), 2004)
The paper discusses the implications of the security factor in the regional development in Algarve region. Considering the goal of sustainable development and growth, some variables related to criminality at regional level have been observed and compared to the national values. The obtained data bases was applied in a methodological essay to search for significant statistical correlations between criminal registers and a set of so-cial and economic indicators, namely: unemployment, internal regional product at mp and cp, regional added value, population density, entered legalised citizens and visiting foreign citizens. This study, developed at regional level, reports an observation period from 1995 and is based on the bibliographic support kindly supplied by the Cabinet of Legislative Politics and Planning in Ministry of Justice. The results show an inexistence of statistical correlation's between the regional unem-ployment rates and the criminal registers. Positive correlations were found for follow-ing indicators: internal regional internal product, regional added value (in what con-cerns crimes against the State and the crimes foreseen in Sundry Legislation). Also the population density reacted positively to the tests of correlation with the group of crimes against the State. The same occurrence was found in the registers of foreign legalized citizens. When the association between the registers of visitors was considered, the cor-relation appeared on the crimes against the State and the crimes foreseen in Sundry Legislation. Despite the Algarve region being classified, for its visitors, as “safe tourist destina-tion”, these associations disclosed some concern about the impact of this type of crime in the regional development logic's to Algarve region, essentially for its tourist pre-ponderance and localisation as peripheral region in the UE. Keywords: Regional Development, Internal Security, Criminal Records GPLP-MJ, Correlations; Social and economic pointers;
Keywords: 330; Regional Development; Internal Security; Criminal Records GPLP-MJ; Correlations; Social and economic pointers